2024
DOI: 10.3390/antibiotics13010072
|View full text |Cite
|
Sign up to set email alerts
|

Translational PK/PD for the Development of Novel Antibiotics—A Drug Developer’s Perspective

Caterina Bissantz,
Claudia Zampaloni,
Pascale David-Pierson
et al.

Abstract: Antibiotic development traditionally involved large Phase 3 programs, preceded by Phase 2 studies. Recognizing the high unmet medical need for new antibiotics and, in some cases, challenges to conducting large clinical trials, regulators created a streamlined clinical development pathway in which a lean clinical efficacy dataset is complemented by nonclinical data as supportive evidence of efficacy. In this context, translational Pharmacokinetic/Pharmacodynamic (PK/PD) plays a key role and is a major contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…The categorization of strains/isolates based on the predominant mechanism of action is particularly important when attempting to establish PK/PD indices for β-lactamase inhibitors with direct antibacterial effects, as well as inhibiting β-lactamase activity. While they have limitations (e.g., [28]), PK/PD indices are extensively used to extrapolate results from nonclinical models to a clinical setting and support clinical dose selection [9][10][11][12][13][29][30][31]. Standard PK/PD indices are believed to reflect the underlying mechanism of antibacterial activity, e.g., C max /MIC is associated with concentration-dependent bactericidal activity, while %T > MIC is associated with time-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The categorization of strains/isolates based on the predominant mechanism of action is particularly important when attempting to establish PK/PD indices for β-lactamase inhibitors with direct antibacterial effects, as well as inhibiting β-lactamase activity. While they have limitations (e.g., [28]), PK/PD indices are extensively used to extrapolate results from nonclinical models to a clinical setting and support clinical dose selection [9][10][11][12][13][29][30][31]. Standard PK/PD indices are believed to reflect the underlying mechanism of antibacterial activity, e.g., C max /MIC is associated with concentration-dependent bactericidal activity, while %T > MIC is associated with time-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that even high doses of nacubactam monotherapy are not effective in in vivo models against some carbapenem-resistant Enterobacterales isolates despite low in vitro nacubactam MICs [45]. In such circumstances, mechanistic or semi-mechanistic PK/PD modeling (e.g., [13,31,[46][47][48]) offers potential advantages over traditional PK/PD indices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation